Effectiveness of Cognitive-Behavioral Hypnotherapy on Pain in Patients with Premenstrual Disorder - Marziyeh Amin Sorkhi; Ramazan Hassanzadeh; Javanshir Asadi; Mehdi Pourasghar (Hamadan University of Medical Sciences, 2023)
Background and Objective: Due to the increasing prevalence of premenstrual disorder and the need to use the most effective treatment to improve the symptoms of this syndrome, this study was conducted to evaluate the effectiveness of cognitive-behavioral hypnotherapy on pain in patients with the premenstrual disorder. Materials and Methods: The study followed a semi-experimental pretest-posttest design with a control and an experimental group. The statistical population of the research included all women aged 25 to 40 who visited a gynecologist at least three times in the past year due to menstrual pain and were referred to a counseling and psychological center with the diagnosis of premenstrual dysphoria. A group of 24 people were selected using the available sampling method and were randomly divided into the experimental and control group (12 people each). The research tool was the Pain Questionnaire. Cognitive-behavioral hypnotherapy intervention was implemented in eight 90-minute sessions for the experimental group. After entering the data into the SPSS software (version 25), they were analyzed by multivariate analysis of covariance (MANCOVA). Results: The results of MANCOVA showed that cognitive-behavioral hypnotherapy significantly improved pain intensity, as well as physical-sensory, sensory-emotional, and cognitive-evaluative aspects of life in women with premenstrual dysphoria (P<0.05). Conclusion: Cognitive-behavioral hypnotherapy improves physical-sensory, sensory-emotional, and cognitive-evaluative aspects of life in women with the premenstrual disorder. It also influences their adaptive and uncompromising strategies, mental health, social relationships, environmental health, general health, and quality of life.